Proliferacja ludzkiej intymności w kontekście politycznych zachowań wyborczych - Januszewicz, Jakub (Refleksje. Pismo naukowe studentów i doktorantów WNPiD UAM, 2015)
This article is an att empt to examine is there any relation between modern meaning and understanding nature of human intimacy and political behaviors during election campaign. We’re searching for evidences which can confirm that our sexuality is one of the most important factors when we choose politicians to represent us. Background of this claim is a movie “Intimacy” directed by Patrice Chéreau. It’s a story about an affair between woman and man, two people who meet once a week to make love. Using this movie as a metaphor we will try to indicate that the reasons we decide to support somebody’s run for office are similar to these, which we involve when we choose our live or sex partners. One of them is based on Personalization of Politics, attitude that politcian’s views, achievements or political program are less crucial than their image.